MICROENVIRONMENTS OF PH IN BIOFILMS GROWN ON DISSOLVING SILICATE SURFACES - Liermann L.J.; Kalinowski B.E.; Brantley S.L.; Barnes A.S.; Zhou X. (My University, 2000)
Differences in pH between silicate–biofilm interfaces and bulk medium (ΔpH=pHinterface−pHbulk) were detectable with commercial microelectrodes in cultures grown in unbuffered medium (|ΔpH|=0.27–1.08) for an arthrobacter species, but were generally beneath detection (ΔpH<0.04) for a streptomyces species. Biofilm half-thicknesses developed by Arthrobacter ranged from 1.2 to 11.5 mm, and were highly variable even for replicates. In buffered medium, neither bacterium produced a measurable ΔpH across the biofilms grown on silicates. The silicates consisted of polished hornblende, synthetic Fe-rich glass similar to hornblende in bulk composition, and two commercially available “float glasses,” one low-Fe and one high-Fe. The two species of soil bacteria investigated are both known to accelerate release of Fe from hornblende. For the Arthrobacter, values of |ΔpH| developed on hornblende crystal or glass substrates were generally larger than those developed on either float glass. Differences in ΔpH developed on different substrates could not be related simply to relative rates of dissolution of substrates.Differences between the two bacterial species are probably related to differences in (1) rates of growth, (2) production of low-molecular-weight organic acids, (3) physical characteristics of polysaccharide slimes excreted and/or (4) production of siderophores. Although values of |ΔpH| developed at mineral–water interfaces in natural systems may not be as large as those measured here except for water-saturated systems, it is probable that significant values of ΔpH (≤pH unit) develop where fast-growing, acid-producing microbes colonize slow-dissolving phases in the presence of unbuffered solutions.